KEBIJAKAN PENGELOLAAN LINGKUNGAN HIDUP YANG BERWAWASAN PEMBANGUNAN BERKELANJUTAN DI ERA OTONOMI DAERAH - Hidayah Hasibuan, Erwin (MEDIA HUKUM, 2014)
The extended development that put the living space as a part of integration in the national dynamic development that becomes a reality of state livem, and because of that the values of extended development is important meaning in the frame of forming legal bilogical environment.